1991
DOI: 10.1246/cl.1991.1611
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Oxide-Based Semiconductor Sensor Highly Sensitive to NO and NO2

Abstract: A sintered sensor element based on WO3 was found to be very sensitive to NO and NO2. The sensitivity, defined as the ratio of the resistance in the gases to that in air, was as high as 31 and 97 to 200 ppm NO and 80 ppm NO2, respectively, at 300 °C. The element was well suited for sensing the gases at low levels. Satisfactory performances to NO and NO2 were exhibited in the regions of 0–800 ppm and 0–200 ppm, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(116 citation statements)
references
References 4 publications
2
113
0
1
Order By: Relevance
“…4,6) Thermal decomposition and pyrolysis of tungsten salt are also common for preparation of the powder for gas sensor application. [7][8] For these methods, the powders are always subjected to heat treatment either during the synthesis step as in the case of thermal decomposition or pyrolysis, or post-synthesis step as in the case of wet chemical processes. Such heat treatment is important as it transforms the material into a desirable composition or crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…4,6) Thermal decomposition and pyrolysis of tungsten salt are also common for preparation of the powder for gas sensor application. [7][8] For these methods, the powders are always subjected to heat treatment either during the synthesis step as in the case of thermal decomposition or pyrolysis, or post-synthesis step as in the case of wet chemical processes. Such heat treatment is important as it transforms the material into a desirable composition or crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…WO 3 has been extensively studied as a material suitable for NO 2 sensing (Chung et al, 1999;Jin et al, 2005) since it was shown that it indicated a higher sensitivity to NO 2 than to CO, H 2 , CH 4 , and i-C 4 H 10 (Akiyama et al, 1991). NO 2 sensors made of WO 3 nanowires have also been studied; the sensors made of nanowires formed by using thermal evaporation (Ponzoni et al, 2006) and solvothermal method (Rout et al, 2006) indicated high sensitivities to NO 2 in the range of parts per billion at high temperatures above 200°C.…”
Section: Wo 3 Nanowires Formed By Vapor Transportmentioning
confidence: 99%
“…(7)(8)(9)(10)(11) Among the metal oxides, n-type tungsten oxide (WO 3 ) appears to be a promising material for use in a NO gas sensor. (8,9) In a previous publication, we reported on the reliable response of a p-type cobalt oxide (Co 3 O 4 ) gas sensor to NO gas at 0.5-5 ppm in air. (10) Furthermore, because that Co 3 O 4 gas sensor showed a low resistance of below 1 kΩ, the peripheral circuit used to measure the sensor resistance does not require a large resistance, reducing the device cost.…”
Section: Introductionmentioning
confidence: 99%